Effect on Multipotency and Phenotypic Transition of Unrestricted Somatic Stem Cells from Human Umbilical Cord Blood after Treatment with Epigenetic Agents - Foued Ghanjati; Simeon Santourlidis (Hindawi Limited, 2016)
The epigenetic mechanism of DNA methylation is of central importance for cellular differentiation processes. Unrestricted somatic stem cells (USSCs) from human umbilical cord blood, which have a broad differentiation spectrum, reside in an uncommitted epigenetic state with partial methylation of the regulatory region of the gene coding for the pluripotency master regulator OCT4. Thus we hypothesized that further opening of this "poised" epigenetic state could broaden the differentiation potential of USSCs. Here we document that USSCs drastically change their phenotype after treatment by a new elaborated cultivation protocol which utilizes the DNA hypomethylating compound 5'-aza-2-deoxycytidine (5-Aza-CdR) and the histone deacetylase inhibitor trichostatin A (TSA). This treatment leads to a new stable, spheroid-forming cell type which we have named SpheUSSC. These cells can be stably propagated over at least 150 cell divisions, express OCT4, retain the potential to undergo osteogenic differentiation, and have additionally acquired the ability to uniformly differentiate into adipocytes, unlike the source USSC population. Here we describe our treatment protocol and provide evidence that it induces a dedifferentiation step and concomitantly the acquisition of an extended differentiation capability of the new SpheUSSC type.